Adalékok a jászói Keresztelo Szent János premontrei monostor középkori történelméhez - Kotrusová, Júlia (Micae mediaevales VII. Fiatal történészek dolgozatai a középkori Magyarországról és Európáról, 2018)
The Monastery of St. John the Baptist in Jasov belongs among the oldest Premonstratensian monasteries in modern Slovakia. The circumstances surrounding the arrival of Premonstratensians in Jasov and the year of foundation of the monastery are amongst the most debated problems in the history of the Jasov provostship. The source of these controversies is the fact that the foundation charter was not preserved. The opinions of historians on the foundation of the monastery vary. A number of historians assume that it was founded at the turn of the 12th and 13th centuries, possibly at the beginning of the 13th century. I argue that a charter issued by King Béla IV in 1255 can contribute to clarification of the foundation of the convent. The document re-establishes the originalprivileges of the monastery. The earliest references to Premonstratensian monasteries in Hungary is preserved in the Ninive catalogue, specifically in its second registry. The properties of the monastery also raise a number of questions. The institution owned properties of high value in the Middle Ages. The oldest mention of their estate possession dates back to the above mentioned charter issued by King Béla IV in 1255. The lands mentioned in the charter were compact. Besides the original property described by the charter, in 1255 lands were provided for the monastery that Béla acquired from Duke Coloman. During the medieval and early modern period Jasov was a central property of the Jasov provostship. Due to its location and its vicinity to the monastery, it became more and more prominent in the 13th century, when it gained urban privileges, most importantly market rights.
Keywords: jasov